Efektivitas Teks Persuasif dalam Strategi Komunikasi Pemasaran Digital di Platform TikTok - Siregar, Feby Yoana (Linguistik, Terjemahan, Sastra (LINGTERSA), 2025)
This study aims to describe the forms and strategies of persuasive sentences usedin sales advertisements on the TikTok platform, focusing on the local account@TikLove.id. The background of this study is based on the importance oflanguage as the main tool in digital marketing communication, especially insocial media that demands speed, interactivity, and an emotional approach to theaudience. The aim is to describe the forms and strategies of persuasive sentencesthey use in advertising content. Using a qualitative descriptive method,researchers collected data in the form of 12 advertising sentences described interms of language form, communicative intent, and persuasive strategies applied.The results show that direct invitation sentences (imperatives) and exclamations(interjections) are most widely used. Strategies such as creating a sense ofurgency, building emotional closeness, and adjusting to the lifestyle of the digitalaudience are key to attracting attention. The novelty of this study lies in its specificapproach exploring persuasive language in short video content that is local,practical, and close to the daily lives of Indonesian people. This study not onlyadds insight into how language works on social media, but also provides a realpicture of how small business actors utilize the right communication style to reachconsumers. This research bridges the gap between linguistic studies and currentdigital marketing practices.